Serum concentrations of levosimendan and its metabolites OR-1855 and OR-1896 in cardiac surgery patients with cardiopulmonary bypass - Kipka, Hannah; Liebchen, Uwe; Hübner, Max; Höfner, Georg; Frey, Otto; Wanner, Klaus T.; Kilger, Erich; Hagl, Christian; Tomasi, Roland; Mannell, Hanna (Frontiers in Cardiovascular Medicine, 2024)
The inotropic drug levosimendan is often used as an individualized therapeutic approach perioperatively in cardiac surgery patients with cardiopulmonary bypass (CPB). Data regarding serum concentrations of levosimendan and its metabolites within this context is lacking.Methods: In this retrospective descriptive proof-of-concept study, total serum concentrations (TSC) and unbound fractions (UF) of levosimendan and its metabolites OR-1896 and OR-1855 in cardiac surgery patients with CPB were measured using LC-ESI-MS/MS. Simulation of expected levosimendan TSC was performed using Pharkin 4.0. Serum NT-proBNP was assessed with ELISA.Results: After levosimendan infusion (1.25mg or 2.5mg, respectively) after anaesthesia induction, a median TSC of 1.9 ng/mL and 10.4 ng/mL was determined in samples taken directly after surgery (T1). Median TSC of 7.6 ng/ml and 22.0 ng/ml, respectively, were simulated at T1. Whereas 1.1 ng/mL and 1.6 ng/mL TSC of OR-1896, respectively, was quantified the day after surgery (T2), TSC of the intermediate metabolite OR-1855 was mostly below the lower limit of quantification (LLOQ). The UF was 0.5% and 1.1% for levosimendan and 64.1% and 52.1% for OR-1896, respectively, with over half the samples being below LLOQ. NT-proBNP concentrations before surgery and T2 did not differ. Discussion: The low TSC, UF and unchanged NT-proBNP levels in combination with high variation of serum levels between patients suggest a need for optimized dosing regimen of levosimendan combined with therapeutic drug monitoring for such an individualized approach. In addition, the differences between the measured and estimated concentrations may suggest a possible influence of CPB on levosimendan serum concentrations.